Evaluación del riesgo volcánico ante una posible erupción del Volcán Callaqui, Chile - Araneda C., Manuel; Avendaño R., María Soledad (Revista Geofísica, 2019)
Ice mass evaluation of the most important glacial areas of Callaqui volcano was made using gravimetric profiles, direct aerial observation and through areal photog- raphy’s analysis. The Callaqui volcano is located in the VIII Region of Chile, geo- graphic coordinates 37° 55’ 20” S and 71° 26’ 50” W. The volcanic eruption of Callaqui volcano can melt the ice cover, water flow through streams and river could damage in Pangue and Ralco hydroelectric power station, located near by the “Bio- Bio” river valley, additionally an indeterminate number of houses and agriculture facilities and not less important human lives. Result of the investigation has proved a total of 0.424168km3 of ice volume plus 3m of snow during winter season. Assuming 0.8gr/cm3 density of the ice and 0.25gr/cm3 for the snow, a total of 0.339334km3 of water would be the flow from Callaqui volcano. The material cost due the volcanic eruption was evaluated in US$2,346x106. Finally is recommended a setting of a monitoring system with special equip- ment.